A Genuine Trivalent Bis-Acylphosphide (BAP) Complex of Uranium - Hochholzer, Jakob; Waldschmidt, Pablo; Heinemann, Frank Wilhelm; Grützmacher, Hansjörg; Meyer, Karsten (European Journal of Inorganic Chemistry, 2024)
The genuine trivalent uranium complex, K[UIII(mesBAP)4], employing four bidentate bis(2,4,6-trimethylbenzoyl)phosphide (mesBAP) chelating ligands, is reported and obtained by the reduction of the literature-known tetravalent analog [UIV(mesBAP)4]. Hence, the bis(acyl)phosphide mesBAP ligand allowed to establish a fully reversible redox couple with uranium in the oxidation states +III and +IV. In both complexes [U(mesBAP)4]0/−, the uranium ions are coordinated to four mesBAP ligands in a square antiprismatic geometry. All new compounds have been characterized by single-crystal XRD analysis, 1H and 31P NMR, and UV/Vis/NIR electronic absorption spectroscopy, as well as SQUID magnetization and electrochemical measurements, and CW X-band EPR in the case of the trivalent complex.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Bisacylphosphide BAP; Ligands; Magnetism; Spectroscopy; Uranium Complexes